A new species of the genus Toccolosida Walker, 1863 from India (Lepidoptera: Pyralidae: Pyralinae) - Singh, Navneet; Chandra, Kailash; Kirti, Jagbir Singh; Ranjan, Rahul (Zootaxa, 2019)
The genus Toccolosida Walker, 1863 is a member of the Pyralini tribe of the subfamily Pyralinae in the family Pyralidae. It was described as a monotypic genus for Toccolosida rubriceps Walker, 1863 from Sikkim. Snellen (1890, 1892) described two additional species of Toccolosida, T. pallifrons Snellen, 1890 from Sikkim and T. bilinealis Snellen, 1892 from Indonesia and Java. Hampson (1896) erected a new genus Proteinia Hampson, 1896 for T. pallifrons. In 1899, Snellen described another species, T. subolivalis Snellen, 1899 from Indonesia, Sumatra and Padang. Robinson et al. (1994) included two species, T. rubriceps and T. bilinealis, in their account on South East Asian moths and stated that Toccolosida contains 8+ [described as well as undescribed] species from the Indo-Australian region and 6+ species from South East Asia. However, at present the valid Toccolosida species are only three: T. rubriceps, T. bilinealis and T. subolivalis, whereas pallifrons is currently placed in Proteinia (Nuss et al. 2003–2019; pers. comm. Dr. Richard Mally, University Museum of Bergen, Natural History Collections, Bergen, Norway).